Pengembangan Komik Digital "KOMJUR" (Komik Kejujuran) sebagai Media Dakwah untuk Memupuk Kejujuran pada Pembelajaran PAI Kelas 2 SD - Lestari, Amalia; Arista, Gina Dwi; Septiani, Vina Siti Nur; Aeni, Ani Nur (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This article discusses the development of digital comics "KOMJUR" (Honesty Comic) as a preaching media in fostering honesty in elementary school students using the Design and Development (D&D) research method with the ADDIE research model, as well as data collection through questionnaires, observations, questionnaires, pre-test, post-test, and gain normality test. This study aims to facilitate PAI learning and as a media for da'wah in order to foster an honest attitude and improve learning outcomes. Based on the results of the study, it shows that the digital comic "KOMJUR" (Honesty Comic) gets a good and positive response from users. The evaluation results indicate that "KOMJUR" (Comic of Honesty) is categorized as effective for fostering students' honest attitudes and improving student learning outcomes, this can be seen during learning where students are more motivated. So that the digital Comic learning media "KOMJUR" (Honesty Comic) can be an alternative learning media in PAI class 2 elementary school subjects.